The Manajemen Pentahelix Dalam Pencegahan Dan Penaggulangan Terorisme Di Desa Kananga Kabupaten Bima - Fuad, Muhammad; Umar; Najamudin (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Terrorism is a crime that is now widely discussed in print and electronic media, especially in Indonesia, which has been seriously affected since the Bali Bombing I in 2002. To this day, acts of terrorism continue to occur in various forms, involving both individuals and groups. This study aims to analyze the implementation of the Penta helix concept in efforts to prevent and counter terrorism in Kananga Village, Bima Regency, as well as to identify the challenges encountered. This research employs a qualitative method with a case study approach involving informants representing the five elements of the Pentahelix: government, academia, business, community, and media. Informants were selected through purposive sampling, and data were collected through interviews, observations, and documentation. The study results show that applying the pentahelix concept through a culturally-based approach, education, and solidarity effectively maintains social harmony and prevents the community from being exposed to radicalism. However, the main challenges faced include a need for coordination among institutions, limited access to vulnerable communities, and negative perceptions from some community members toward these efforts. The study concludes that the Penta helix concept can create a positive synergy between the government, academia, business, community, and media. However, challenges in coordination and perception need to be addressed to maximize its effectiveness in preventing terrorism